PENGARUH MOTIVASI KERJA DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN DI HOTEL SANTIKA KOTA TASIKMALAYA - Arip Rahman Hakim; Kusuma Agdhi Rahwana; Arga Sutrisna (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2023)
This study aims to determine and analyze the effect of work motivation and organizational culture on employee job satisfaction at Hotel Santika Tasikmalaya City. This research is a quantitative research through causality method with survey approach. The research sample taken was 60 employees of Hotel Santika Tasikmalaya. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results showed that work motivation had a very good assessment classification, organizational culture had a very good assessment classification, while job satisfaction had a good classification for employees of Hotel Santika Tasikmalaya City. Together, work motivation and organizational culture have a significant influence on job satisfaction for employees at Hotel Santika, Tasikmalaya City. Partially, work motivation has a significant effect on job satisfaction for employees of Hotel Santika, Tasikmalaya City. Partially, Organizational Culture has a significant effect on Job Satisfaction on Employees of Hotel Santika Tasikmalaya City